Translating policy into practice : challenges in the implementation of Local Economic Development (LED) Projects in Greater Tzaneen Municipality in Limpopo Province - Malele, L. E.; Moyo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
Local Economic Development (LED) is an important strategy which the South African government introduced in order to achieve socio-economic development at the local level. It aims to boost economic activities that benefit local communities in a sustainable manner and also to enhance the competitiveness of the local economy. Cognisant of its development potential, the government has developed a National LED Policy Framework in order to guide municipalities. The study focuses on the Greater Tzaneen Municipality in Limpopo Province. Although it has implemented many LED projects in the context of Integrated Development Planning (IDP), the translation of the LED policy into practice has been limited. The study therefore aims to develop a more holistic understanding of the dynamics of local economic development initiatives and implementation challenges in the municipality. Its ultimate objective is to explore options to address those challenges so as to ensure that policy effectively achieves the intended results. The research adopts a qualitative research design. Its rationale was to gain more in-depth knowledge and insights on the dynamics and complexities of the translating LED policy into practice. Face to face interviews were used to collect data from a small sample of 10 participants composed of project participants and municipal officials. The paper presents findings that point to limited success in implementation of LED, with major challenges consisting of obstacles posed by outstanding land claims and also the lack of the necessary financial and human resource capacity required. The paper’s value addition lies in the presentation of the myriad of management challenges in the context of the municipality and the subsequent recommendations towards improving LED implementation.
Journal article published in the International Conference on Public Administration and Development Alternatives
Keywords: Local economic development; Local government; Outstanding land claims; Sustainability; Economic development -- South Africa -- Limpopo; Sustainable development -- South Africa -- Limpopo; Economic development projects -- South Africa; Local government -- South Africa -- Limpopo